Strengthening the procedural fidelity research‐to‐practice loop in animal behavior. Issue 2 (5th July 2022) - Kodak, Tiffany; Bergmann, Samantha; Waite, Mindy
Abstract : Procedural fidelity is the extent to which components of an intervention are implemented as designed. Procedural fidelity is measured as a dependent variable and manipulated as an independent variable. In research and practice, procedural‐fidelity data should be collected, monitored, and reported. Procedural fidelity as an independent variable has been investigated in humans using parametric analyses, and the current article summarizes some of the research conducted on the effects of procedural‐fidelity errors in behavior‐reduction and skill‐acquisition interventions. Connections were drawn to applied animal researchers and the work of animal behavior practitioners to produce implications for practice with human and animal clients and suggestions for future research. Further, there are multiple ways to measure procedural fidelity, and different conclusions can be drawn based on the measure and computation method. The current article describes procedural‐fidelity measures that are most applicable to animal behavior researchers and professionals.